“Peace Lecture”: Curricular Proposal to Strengthen Coexistence - Betancourt Rodríguez, Milton Andrés; Triana Rivera, Reyes; Torres Quitora, Luis Fernando (Rastros Rostros, 2017)
Introduction: This  article  is  a  curricular  proposal  for  a  peace  lecture  to  strengthen  the  healthy  coexistence  of  students,  based  on  Law  1732  of  2014,  which systematizes  and  contextualizes  the  reality,  objectives,  principles  and  methodological and didactic foundations that must be adopted by each institution (P,1).Materials and methods: Qualitative research. The results are achieved through surveys and interviews of students and teachers, which demonstrate the importance  of  implementing  the  curricular  proposal  for  a  peace  lecture  that  helps  to  reduce  school  conflicts  and  strengthen  coexistence  among  classmates. Results: It was observed that the implementation of a peace lecture through the activities and workshops carried out, and the use of ict , reduced school conflicts among students.Conclusion:   A  peace  lecture  should  focus  on  education  as  a  primary  factor  for  students  through  the  proper  management  of  the  principles  of  peace,  peace education and school conflicts, as well as the causes and consequences that have been identified in the research.
Keywords: peace lecture; triadic brain; coexistence; curriculum; peace education